Answer:
3yz² - 3z² - 5y + 7
Step-by-step explanation:
Sum of two polynomials = –yz² - 3z² – 4y + 4
One of the polynomial = y - 4yz²- 3
Find the other polynomial
The other polynomial = sum of the polynomials - one of the polynomial
= –yz² - 3z² – 4y + 4 - (y - 4yz² - 3)
= –yz² - 3z² – 4y + 4 - y + 4yz² + 3
= -yz² + 4yz² - 3z² - 4y - y + 4 + 3
= 3yz² - 3z² - 5y + 7
A. 0 -2yz?
B. – 4y + 7 01 - 2yz
C. – 3y + 1 0 -5yz² + 3z² – 3y + 1 D. 3yz² - 3z² – 5y + 7
Answer:
2919.9455657092 centimeters^2
Step-by-step explanation:
Answer:
Step-by-step explanation:
-2x - 14 > -4 + 3x
subtract 3x from both sides
-5x - 14 > -4
add 14 to both sides
-5x > 10
divide both sides by -5
x < -2
Answer:
Step-by-step explanation:
F(x)=e^(4x)+e^(4x) =2e^(4x)